Family firms, soft information and bank lending in a financial crisis - D'Aurizio, Leandro; Oliviero, Tommaso; Romano, Livio (Journal of Corporate Finance, 2015)
This paper studies differences in family and non-family firms' access to bank lending during the 2007–2009 financial crisis. The hypothesis is that the former's incentive structure results in less agency conflict in the borrower–lender relationship. Using highly detailed data on bank–firm relations, we exploit the reduction in bank lending in Italy following the crisis in October 2008. We find statistically and economically significant evidence that credit to family firms contracted less sharply than that to non-family firms. The results are robust to observable ex-ante differences between the two types of firms and to time-varying bank fixed effects. We show, further, that the difference is related to an increased role for soft information in some Italian banks' operations, following the Lehman Brothers failure. Finally, by identifying a match between those banks and family firms, we can control for time-varying unobserved heterogeneity among the firms and validate the hypothesis that our results are supply-driven.